An EFL Teacher Candidates Teaching Experience from Action Research and Intercultural Communicative Competence (Papeles, 2017)
Language teacher candidates have been experiencing their practicum through action research as a supportive path for teacher reflective practice. They are also using intercultural communicative competence lenses through art in their EFL classrooms in order to address diversity and make their pedagogy relevant to their school students. This paper presents an advance on a collaborative action research that addresses the questions: how can collaborative action research support teaching first experiences?, and how do teacher candidates address diversity and cultural issues in their classrooms?